Is match playing time a potential tool for managing load in women's handball? - García-Sánchez, C.; Navarro, R. M.; Nieto-Acevedo, R.; de la Rubia, A. (The Journal of Strength and Conditioning Research, 2024)
The aim of this study was to explore the external load experienced by female handball players according to the time played in official matches (=40, <40, and =20 minutes) and in relation to playing positions (backs, pivots, and wings). Twenty-two female players from the Spanish second Division were monitored across 13 matches. Total distance covered, high-speed running distance (HSR), accelerations, decelerations, and PlayerLoad were collected in absolute and relative values using a local positioning system (WIMU PRO, Realtrack Systems SL, Almería, Spain). One-way ANOVA with partial eta-squared and Cohen's d were used to determine the differences between playing time groups and between playing positions. This study revealed that players with more match playing time had a higher absolute values in all external load variables (p < 0.001; very large effects), except in HSR where only wings showed higher values according to the time played (p < 0.001; very large effects). However, these differences between playing time groups disappear when the external load values were normalized according to the effective playing time (p > 0.05). In relation to playing positions, wings covered more HSR/minutes than the other playing positions regardless of the playing time (p < 0.05; large effects). In addition, backs performed more ACC/minutes than wings in the high playing time group and more than pivots in the low playing time group (p < 0.05, moderate effects). In addition, backs performed more DEC/minutes than wings in the low playing time group (p < 0.05, moderate effects). Therefore, handball coaches should consider the playing time as an effective tool to optimize the weekly load distribution.